Host-guest composite material based on metal organic framework material and N4Py high-valence mononuclear iron complex as well as preparation method and application of host-guest composite material

By using the host-guest composite of the metal organic framework material UiO-66-F4 and N4Py high-valent mononuclear iron complex in homogeneous reaction, the dimerization loss of bionic non-heme high-valent iron complex in homogeneous reaction is solved. The problem of survival achieves highly reactive and selective hydrocarbon activation.

CN119192601AActive Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411381504.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Bionic non-heme high-valent iron complexes are prone to form dipolymerized oxygen-bridged binuclear trivalent iron complexes during homogeneous reactions, resulting in loss of catalytic activity.

Method used

The host-guest composite material based on metal organic frame material and N4Py high-valent mononuclear iron complex is used, and the porous coordination polymer material with UiO-66-F4 as the host and [(N4Py)FeIV=O]Cl2 as the guest is used. The pore structure of UiO-66-F4 forms a strong interaction with the iron complex, stabilizing it in a homogeneous reaction.

Benefits of technology

The reaction activity and selectivity are improved, the inactivation problem of high-valent iron complexes in dimerization in homogeneous reactions is avoided, and the catalytic activity is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192601A_ABST
    Figure CN119192601A_ABST
Patent Text Reader

Abstract

The invention discloses a host-guest composite material based on a metal organic framework material and an N4Py high-valence mononuclear iron complex as well as a preparation method and application of the host-guest composite material, and relates to the technical field of porous coordination polymer materials. The preparation method is used for solving the technical problem that an existing bionic non-heme high-valence iron complex is extremely prone to dimerization in the homogeneous reaction process to form an oxygen-bridged binuclear ferric iron complex, and then the catalytic activity of the bionic non-heme high-valence iron complex is lost. The preparation method of the host-guest composite material comprises the following steps: obtaining UiO-66-F4 powder and an acetonitrile solution containing a divalent mononuclear iron complex; the method comprises the following steps: adding UiO-66-F4 powder into an acetonitrile solution, and stirring until a divalent mononuclear iron complex enters the interior of a UiO-66-F4 structure, so as to obtain FeN4Py-coated UiO-66-F4; the FeN4Py-coated UiO-66-F4 is placed in an acetonitrile aqueous solution containing ceric ammonium nitrate, and after standing, the subject-object composite material is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous coordination polymer materials, and more specifically, to a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, and a preparation method and application thereof. Background Art

[0002] With the accelerated advancement of global industrialization, human society's demand for various high-value chemicals continues to grow. Among them, the activation of CH bonds is a key step in the conversion process from primary chemicals to high-value chemicals, and has always been a research hotspot in the field of chemical catalysis.

[0003] Biomimetic non-heme high-valent iron complexes show extremely high reactivity and selectivity in the activation process of hydrocarbons. One of the most representative non-heme mononuclear high-valent iron complexes ([(N4Py)Fe IV =O] 2+ ), its ability to activate CH bonds is even higher than that of its biological reference P450, and it can activate high bond energy (99.3kcal / mol) CH bonds at room temperature. However, this type of biomimetic non-heme high-valent iron complex is very easy to dimerize to form oxygen-bridged binuclear trivalent iron complexes during homogeneous reactions, resulting in the loss of catalytic activity. Summary of the invention

[0004] The purpose of the present invention is to provide a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, as well as a preparation method and application thereof, to solve the technical problem that the existing biomimetic non-heme high-valent iron complex is very easy to dimerize to form an oxygen-bridged binuclear trivalent iron complex during a homogeneous reaction, thereby causing it to lose its catalytic activity. In view of this, the present invention is implemented through the following technical solutions.

[0005] In a first aspect, the present invention provides a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, wherein the structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

[0006] Compared with the prior art, the host-guest composite material based on metal organic framework material and N4Py high-valent mononuclear iron complex of the present invention is based on UiO-66-F4 as the main component and [(N4Py)Fe IV =O]Cl2 is the guest, and the high-valent iron complex [(N4Py)Fe IV =O]Cl2 and the pore structure of UiO-66-F4 can form a strong interaction force, and have high stability. The host-guest composite material of the present invention is used for the activation of hydrocarbons in a homogeneous reaction process, and it shows high reactivity and selectivity, solving the technical problem that the existing biomimetic non-heme high-valent iron complex is very easy to dimerize to form an oxygen-bridged binuclear trivalent iron complex in a homogeneous reaction process, thereby causing it to lose its catalytic activity.

[0007] In a second aspect, the present invention provides a method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, which is used to prepare the host-guest composite material, comprising: Obtaining UiO-66-F4 powder and an acetonitrile solution containing a divalent mononuclear iron complex, wherein the divalent mononuclear iron complex is FeN4Py; Adding the UiO-66-F4 powder to the acetonitrile solution, stirring until FeN4Py enters the interior of the UiO-66-F4 structure, and obtaining FeN4Py@UiO-66-F4 after centrifugation and washing; The FeN4Py@UiO-66-F4 was placed in an acetonitrile aqueous solution containing ammonium cerium nitrate and allowed to stand for 30 to 60 minutes to obtain a structural expression of [(N4Py)Fe IV =O]Cl2@UiO-66-F4 said host-guest composite material.

[0008] Compared with the prior art, the beneficial effects of the preparation method of the host-guest composite material based on metal organic framework material and N4Py high-valent mononuclear iron complex of the present invention are the same as the beneficial effects of the host-guest composite material based on metal organic framework material and N4Py high-valent mononuclear iron complex described in the above technical scheme, and will not be repeated here.

[0009] Furthermore, in the preparation method of the host-guest composite material based on metal organic framework material and N4Py high-valent mononuclear iron complex of the present invention, in the process of adding the UiO-66-F4 powder to the acetonitrile solution, the molar ratio of UiO-66-F4 to FeN4Py is 1: (1~2.5).

[0010] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the FeN4Py@UiO-66-F4 is placed in an acetonitrile aqueous solution containing ammonium cerium nitrate, and the molar ratio of FeN4Py to ammonium cerium nitrate is 1: (2~2.5).

[0011] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the volume ratio of water to acetonitrile in the acetonitrile aqueous solution is 1: (1-3).

[0012] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the stirring rate is 100~300rpm and the stirring time is 12~50 hours during the stirring process until FeN4Py enters the interior of the UiO-66-F4 structure.

[0013] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the UiO-66-F4 powder is obtained, comprising: Obtain a glacial acetic acid solution having a volume concentration of 60-70%; Adding tetrafluoroterephthalic acid and zirconium nitrate to the glacial acetic acid solution, and stirring until the solid powder is completely dissolved to obtain a mixed solution; the molar ratio of the tetrafluoroterephthalic acid to the zirconium nitrate is 1: (1-2); The mixed solution is condensed and refluxed at a temperature of 100-120° C. for 24-36 hours to form UiO-66-F4 with a cage-like porous structure; and the UiO-66-F4 is dried to obtain the UiO-66-F4 powder.

[0014] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, after the UiO-66-F4 with a cage-like porous structure is formed and before the UiO-66-F4 is dried, it also includes: Centrifuging the mixed solution to remove the mother liquor to obtain a powdered solid material; Washing the solid material with ultrapure water to remove the solution on the surface of the solid material; The solid material is then immersed in methanol, dichloromethane and acetonitrile for three days, with the solvent changed every day; the solid material is UiO-66-F4.

[0015] Furthermore, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the drying of the UiO-66-F4 comprises: After the solid material was immersed in methanol, dichloromethane and acetonitrile for exchange for three days, the solid material was placed in a vacuum oven at 120° C. for 24 hours and cooled to room temperature to obtain the UiO-66-F4 powder.

[0016] In a third aspect, the present invention provides the use of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex in the preparation of redox catalytic materials and bioinorganic chemical materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 The host-guest composite material of the present invention [(N4Py)Fe IV =O]Cl2@UiO-66-F4 synthesis schematic diagram; Figure 2 Inventive Example 2, the UiO-66-F4 sample and [(N4Py)Fe IV =O]Cl2@UiO-66-F4 XRD comparison spectrum; Figure 3 The UiO-66-F4 sample in Example 2 of the present invention and [(N4Py)Fe IV =O]Comparison of TGA curves of Cl2@UiO-66-F4 samples; Figure 4 The UiO-66-F4 sample in Example 2 of the present invention and [(N4Py)Fe IV =O]Cl2@UiO-66-F4 sample 77K nitrogen adsorption curve comparison; Figure 5 [(N4Py)Fe IV =O]Cl2@UiO-66-F4 sample TEM-EDS spectrum; Figure A is [(N4Py)Fe IV =O]Cl2@UiO-66-F4 sample TEM image, Figure B is [(N4Py)Fe IV =O]Cl2@UiO-66-F4 sample EDS spectrum of fluorine element, Figure C is [(N4Py)Fe IV =O]Cl2@UiO-66-F4 sample EDS spectrum of zirconium element, Figure D is [(N4Py)Fe IV =O] EDS spectrum of iron in the Cl2@UiO-66-F4 sample; Figure 6The UiO-66-F4 sample in Example 2 of the present invention and [(N4Py)Fe IV =O]Cl2@UiO-66-F4 solid ultraviolet spectrum curve comparison chart; Figure 7 This is a reaction pathway diagram for the inactivation of existing non-heme high-valent iron complexes. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.

[0021] Biomimetic non-heme high-valent iron complexes show extremely high reactivity and selectivity in the activation process of hydrocarbons. One of the most representative non-heme mononuclear high-valent iron complexes ([(N4Py)Fe IV =O] 2+ ), its ability to activate CH bonds is even higher than that of its biological reference P450, and it can activate high bond energy (99.3kcal / mol) CH bonds at room temperature. However, this type of biomimetic non-heme high-valent iron complex is very easy to dimerize to form oxygen-bridged binuclear trivalent iron complexes during homogeneous reactions, resulting in the loss of catalytic activity.

[0022] In order to solve the above technical problems, in the first aspect, the present invention provides a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, wherein the structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

[0023] In the case of adopting the above technical scheme, the present invention is based on the host-guest composite material of metal organic framework material and N4Py high-valent mononuclear iron complex, with UiO-66-F4 as the main body and [(N4Py)Fe IV =O]Cl2 is the guest, and the high-valent iron complex [(N4Py)Fe IV =O]Cl2 and the pore structure of UiO-66-F4 can form a strong interaction force, and have high stability. The host-guest composite material of the present invention is used for the activation of hydrocarbons in a homogeneous reaction process, and it shows high reactivity and selectivity, solving the technical problem that the existing biomimetic non-heme high-valent iron complex is very easy to dimerize to form an oxygen-bridged binuclear trivalent iron complex in a homogeneous reaction process, thereby causing it to lose its catalytic activity.

[0024] In the above host-guest composite materials, UiO-66-F4 is a metal organic framework material, [(N4Py)Fe IV =O]Cl2 molecular structure is shown below: .

[0025] [(N4Py)Fe IV =O]Cl2 In a second aspect, the present invention provides a method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, which is used to prepare the host-guest composite material, and the method comprises: Obtaining UiO-66-F4 powder and an acetonitrile solution containing a divalent mononuclear iron complex, wherein the divalent mononuclear iron complex is FeN4Py; Adding the UiO-66-F4 powder to the acetonitrile solution, stirring until FeN4Py enters the interior of the UiO-66-F4 structure, and obtaining FeN4Py@UiO-66-F4 after centrifugation and washing; The FeN4Py@UiO-66-F4 was placed in an acetonitrile aqueous solution containing ammonium cerium nitrate and allowed to stand for 30 to 60 minutes to obtain a structural expression of [(N4Py)Fe IV =O]Cl2@UiO-66-F4 said host-guest composite material.

[0026] When the above technical scheme is adopted, in the preparation method of the host-guest composite material based on metal organic framework material and N4Py high-valent mononuclear iron complex of the present invention, UiO-66-F4 is a metal organic framework (MOF) material, and in the acetonitrile solution, the divalent mononuclear iron complex (such as FeN4Py) exists in a dissolved state, which is conducive to interacting with the pore structure of UiO-66-F4, and acetonitrile is used as the solvent of the divalent mononuclear iron complex, which helps to maintain the stability of the divalent mononuclear iron complex and can fully diffuse in the solvent without destroying the pore structure of UiO-66-F4. The UiO-66-F4 powder is added to the acetonitrile solution. Through stirring, the divalent mononuclear iron complex (guest) in the acetonitrile solution can diffuse and enter the pore structure of UiO-66-F4 (host), thereby initially forming a host-guest composite material FeN4Py@UiO-66-F4; further, the FeN4Py@UiO-66-F4 is placed in an acetonitrile aqueous solution containing ammonium cerium nitrate, and the divalent mononuclear iron complex (FeN4Py) is oxidized to a high-valent state [(N4Py)Fe IV =O]Cl2, and the final host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4.

[0027] The divalent mononuclear iron complex of the present invention uses FeN4Py. Compared with FeN4Py, the high-valent [(N4Py)Fe IV =O]Cl2 has a stronger interaction with UiO-66-F4, which makes the host-guest composite material more stable. In the above process, ammonium cerium nitrate is a strong oxidant that can oxidize the divalent mononuclear iron complex (FeN4Py) to a higher valence state under mild conditions; the use of acetonitrile aqueous solution allows the oxidation process to proceed under homogeneous conditions, which is conducive to full contact between the oxidant (ammonium cerium nitrate) and the reactant. The above FeN4Py molecular structure is shown below: .

[0028] It should be understood that in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, in order to further improve the stability, reactivity and selectivity of the prepared host-guest composite material, in the process of adding the UiO-66-F4 powder to the acetonitrile solution, the mixing ratio of UiO-66-F4 and FeN4Py should also be controlled within a reasonable range. For example, the molar ratio of UiO-66-F4 to FeN4Py can be 1: (1~2.5); for another example, the molar ratio of UiO-66-F4 to FeN4Py can be 1:1, 1:2 or 1:2.5.

[0029] It should also be understood that in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, in order to further improve the stability, reactivity and selectivity of the prepared host-guest composite material, the FeN4Py@UiO-66-F4 is placed in an acetonitrile aqueous solution containing ammonium cerium nitrate, and the mixing ratio of FeN4Py and ammonium cerium nitrate, as well as the concentration of the acetonitrile aqueous solution should be controlled within a reasonable range. For example, the molar ratio of FeN4Py to ammonium cerium nitrate can be 1: (2~2.5), and the volume ratio of water to acetonitrile in the acetonitrile aqueous solution is 1: (1~3); for another example, the molar ratio of FeN4Py to ammonium cerium nitrate can be 1:2, 1:2.2 or 1:2.5, and the volume ratio of water to acetonitrile in the acetonitrile aqueous solution can be 1:1, 1:2 or 1:3.

[0030] It should also be understood that in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, in order to allow FeN4Py to fully enter the interior of the UiO-66-F4 structure and improve the preparation efficiency of the above-mentioned host-guest composite material, the stirring rate and stirring time should also be controlled within a reasonable range. For example, the stirring rate can be 100~300rpm, and the stirring time can be 12~50 hours; for another example, the stirring rate can be 100rpm, 200rpm or 300rpm, and the stirring time can be 12 hours, 20 hours, 30 hours, 40 hours, or 50 hours.

[0031] As a possible implementation mode, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, the step of obtaining the UiO-66-F4 powder comprises: Obtain a glacial acetic acid solution having a volume concentration of 60-70%; Adding tetrafluoroterephthalic acid and zirconium nitrate to the glacial acetic acid solution, and stirring until the solid powder is completely dissolved to obtain a mixed solution; the molar ratio of the tetrafluoroterephthalic acid to the zirconium nitrate is 1: (1-2); The mixed solution is condensed and refluxed at a temperature of 100-120° C. for 24-36 hours to form UiO-66-F4 with a cage-like porous structure; and the UiO-66-F4 is dried to obtain the UiO-66-F4 powder.

[0032] In the case of adopting the above technical scheme, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, glacial acetic acid in an appropriate concentration range is used to fully dissolve the solute (tetrafluoroterephthalic acid and zirconium nitrate) to form a uniform mixed solution; during the process of condensing and refluxing the mixed solution at a temperature of 100-120° C. for 24-36 hours, tetrafluoroterephthalic acid is an organic ligand, and the ligand and zirconium nitrate (providing metal ions Zr 4+ ) undergoes coordination reaction to form UiO-66-F4 with a metal-organic framework structure.

[0033] As a possible implementation mode, in the preparation method of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex of the present invention, after the UiO-66-F4 with a cage-like porous structure is formed and before the UiO-66-F4 is dried, the method further comprises: Centrifuging the mixed solution to remove the mother liquor to obtain a powdered solid material; Washing the solid material with ultrapure water to remove the solution on the surface of the solid material; The solid material is then immersed in methanol, dichloromethane and acetonitrile for three days, with the solvent changed every day; the solid material is UiO-66-F4.

[0034] When the above technical solution is adopted, the purity of UiO-66-F4 can be further improved, and the pore environment of UiO-66-F4 can be optimized. For example, the UiO-66-F4 can be dried by immersing the solid material in methanol, dichloromethane and acetonitrile for three days, then placing the solid material in a vacuum oven at 120°C for 24 hours, and cooling it to room temperature to obtain the UiO-66-F4 powder.

[0035] In a third aspect, the present invention provides the use of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex in the preparation of redox catalytic materials and bioinorganic chemical materials.

[0036] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.

[0037] Unless otherwise specified, the raw materials used in the following examples are commercially available.

[0038] It should be noted that the [(N4Py)Fe IV =O] The molecular structures of Cl2 and FeN4Py are shown above and will not be repeated in the following examples. Example 1

[0039] This embodiment provides a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex. The structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

[0040] This embodiment also provides a method for preparing the host-guest composite material, comprising: S100, weigh 25 mg of FeN4Py into a glass vial and add 4 mL of acetonitrile solution; S200, adding 100 mg of UiO-66-F4 powder to the glass vial, stirring the glass vial open for 50 hours at a stirring rate of 300 rpm, removing the mother liquor by centrifugation, and washing the unreacted FeN4Py with acetonitrile to obtain an orange-yellow powder, which is FeN4Py@UiO-66-F4; wherein the molar ratio of UiO-66-F4 to FeN4Py is 1:1; S300, weighing 15 mg of ammonium cerium nitrate and dissolving it in 0.5 mL of ultrapure water, ultrasonically dissolving it, to obtain an ammonium cerium nitrate solution; S400, weigh 100 mg of FeN4Py@UiO-66-F4 in step S300, and add it to 4.5 mL of acetonitrile aqueous solution, add the cerium ammonium nitrate solution in step S300 to the acetonitrile aqueous solution, let it stand for 30 minutes, and then filter out the mother liquor to obtain a blue-green powder, which is the host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4; wherein the volume ratio of acetonitrile to ultrapure water in the acetonitrile aqueous solution is 2:1, and the molar ratio of FeN4Py to ammonium cerium nitrate is 1:2.

[0041] Furthermore, the UiO-66-F4 in step S200 of this embodiment is prepared by the following steps: S201, weigh 1.19 g (5 mmol) of tetrafluoroterephthalic acid and 2.23 g (5.2 mmol) of zirconium nitrate (Zr(NO3)4·xH2O), and dissolve them in a solution consisting of 20 mL of glacial acetic acid and 30 mL of water to obtain a mixed solution; S202, heating the mixed solution to 105° C. and stirring for 15 min until the solid powder is completely dissolved; S203, after condensing and refluxing the mixed solution at the temperature of step S202 (105° C.) for 30 hours, centrifuge to remove the mother liquor, and obtain a powdered solid material; S204, washing the solid material with ultrapure water for 3 times to remove the surface solution, and exchanging with methanol, dichloromethane and acetonitrile for 3 days respectively, replacing fresh solvent every day; S205, the solid material after solvent exchange is placed in a vacuum oven at 120° C. for 24 hours, cooled to room temperature, and white powder UiO-66-F4 is obtained. Example 2

[0042] This embodiment provides a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex. The structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

[0043] This embodiment also provides a method for preparing the host-guest composite material, comprising: S100, weigh 50 mg of FeN4Py into a glass vial and add 4 mL of acetonitrile solution; S200, adding 100 mg of UiO-66-F4 powder into the glass vial, stirring the glass vial open for 24 hours at a stirring rate of 100 rpm, removing the mother liquor by centrifugation, and washing the unreacted FeN4Py with acetonitrile to obtain an orange-yellow powder, which is FeN4Py@UiO-66-F4; wherein the molar ratio of UiO-66-F4 to FeN4Py is 1:2; S300, weighing 15 mg of ammonium cerium nitrate and dissolving it in 0.5 mL of ultrapure water, ultrasonically dissolving it, to obtain an ammonium cerium nitrate solution; S400, weigh 100 mg of FeN4Py@UiO-66-F4 in step S300, and add it to 4.5 mL of acetonitrile aqueous solution, add the cerium ammonium nitrate solution in step S300 to the acetonitrile aqueous solution, let it stand for 30 minutes, and then filter out the mother liquor to obtain a blue-green powder, which is the host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4; wherein the volume ratio of acetonitrile to ultrapure water in the acetonitrile aqueous solution is 1:1, and the molar ratio of FeN4Py to ammonium cerium nitrate is 1:2.

[0044] Furthermore, the UiO-66-F4 in step S200 of this embodiment is prepared by the following steps: S201, weigh 1.19 g (5 mmol) of tetrafluoroterephthalic acid and 2.23 g (5.2 mmol) of zirconium nitrate (Zr(NO3)4·xH2O), and dissolve them in a solution consisting of 20 mL of glacial acetic acid and 30 mL of water to obtain a mixed solution; S202, heating the mixed solution to 120° C. and stirring for 15 min until the solid powder is completely dissolved; S203, after condensing and refluxing the mixed solution at the temperature of step S202 (120° C.) for 24 hours, centrifuge to remove the mother liquor, and obtain a powdered solid material; S204, washing the solid material with ultrapure water for 3 times to remove the surface solution, and exchanging with methanol, dichloromethane and acetonitrile for 3 days respectively, replacing fresh solvent every day; S205, the solid material after solvent exchange is placed in a vacuum oven at 120° C. for 24 hours, cooled to room temperature, and white powder UiO-66-F4 is obtained. Example 3

[0045] This embodiment provides a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex. The structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

[0046] This embodiment also provides a method for preparing the host-guest composite material, comprising: S100, weigh 62.5 mg of FeN4Py into a glass vial and add 4 mL of acetonitrile solution; S200, adding 100 mg of UiO-66-F4 powder to the glass vial, stirring the glass vial open for 12 hours at a stirring rate of 200 rpm, centrifuging to remove the mother liquor, and washing the unreacted FeN4Py with acetonitrile to obtain an orange-yellow powder, which is FeN4Py@UiO-66-F4; wherein the molar ratio of UiO-66-F4 to FeN4Py is 1:2.5; S300, weighing 19 mg of ammonium cerium nitrate and dissolving it in 0.5 mL of ultrapure water, ultrasonically dissolving it, to obtain an ammonium cerium nitrate solution; S400, weigh 100 mg of FeN4Py@UiO-66-F4 in step S300, and add it to 4.5 mL of acetonitrile aqueous solution, add the cerium ammonium nitrate solution in step S300 to the acetonitrile aqueous solution, let it stand for 30 minutes, and then filter out the mother liquor to obtain a blue-green powder, which is the host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4; wherein the volume ratio of acetonitrile to ultrapure water in the acetonitrile aqueous solution is 3:1, and the molar ratio of FeN4Py to ammonium cerium nitrate is 1:2.5.

[0047] Furthermore, the UiO-66-F4 in step S200 of this embodiment is prepared by the following steps: S201, weigh 1.19 g (5 mmol) of tetrafluoroterephthalic acid and 2.23 g (5.2 mmol) of zirconium nitrate (Zr(NO3)4·xH2O), and dissolve them in a solution consisting of 20 mL of glacial acetic acid and 30 mL of water to obtain a mixed solution; S202, heating the mixed solution to 100° C. and stirring for 15 min until the solid powder is completely dissolved; S203, condensing and refluxing the mixed solution at the temperature of step S202 (100° C.) for 36 hours, and then centrifuging to remove the mother liquor to obtain a powdered solid material; S204, washing the solid material with ultrapure water for 3 times to remove the surface solution, and exchanging with methanol, dichloromethane and acetonitrile for 3 days respectively, replacing fresh solvent every day; S205, the solid material after solvent exchange is placed in a vacuum oven at 120° C. for 24 hours, cooled to room temperature, and white powder UiO-66-F4 is obtained.

[0048] Through the above-mentioned Examples 1 to 3, host-guest composite materials [(N4Py)Fe IV=O]Cl2@UiO-66-F4. In the above embodiment, the present invention synthesized [(N4Py)Fe IV =O]Cl2@UiO-66-F4 system. In simple terms, the two-step in-situ oxidation synthesis method is as follows: first, the divalent mononuclear iron complex (FeN4Py) is loaded into the pores of UiO-66-F4 by immersion, and then the oxidant ammonium cerium nitrate is diffused into the cage cavity of UiO-66-F4 in an acetonitrile aqueous solution, and the divalent mononuclear iron complex (FeN4Py) is oxidized into a tetravalent mononuclear iron complex in the cage cavity, thereby obtaining the host-guest assembled [(N4Py)Fe IV =O]Cl2@UiO-66-F4, specific assembly diagram Figure 1 As shown. The [(N4Py)Fe IV =O]Cl2@UiO-66-F4 host-guest system can completely avoid the high-valent iron complexes from dimerizing easily to form oxygen-bridged binuclear trivalent iron complexes during homogeneous reaction, which leads to their inactivation, and solves the technical problem of its instability from the root. The specific principle is: the cage-like channels of UiO-66-F4 spontaneously transfer the high-valent iron complex ([(N4Py)Fe IV =O]Cl2) is isolated in small rooms, thus effectively blocking the reaction pathway of intermolecular dimerization inactivation. Figures 2 to 6 The host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4 is taken as an example to explain the host-guest composite material of the present invention in detail.

[0049] See also Figures 2 to 6 ,from Figure 2 It can be seen that [(N4Py)Fe IV =O]Cl2@UiO-66-F4 is compared with the X-ray diffraction (XRD) pattern of UiO-66-F4. IV =O]Cl2@UiO-66-F4 has no substantial change in the framework structure of UiO-66-F4, that is, the present invention loads [(N4Py)Fe IV =O]Cl2 will not destroy the pore structure of UiO-66-F4, and the framework of UiO-66-F4 remains stable. Figure 3 The TGA curve (thermal gravimetric curve) shows that compared with the framework material without encapsulated guest molecules (UiO-66-F4), the encapsulated host-guest system ([(N4Py)Fe IV=O]Cl2@UiO-66-F4) has a small weight loss in the range of 200-300°C, which corresponds to the weight loss of the pure tetravalent mononuclear complex, which indirectly confirms that the guest molecule ([(N4Py)Fe IV =O]Cl2) was successfully encapsulated in the pores of UiO-66-F4.

[0050] In order to further verify the high-valent mononuclear complex ([(N4Py)Fe IV =O]Cl2) was successfully encapsulated in the pores of UiO-66-F4, and the host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4 was tested for nitrogen adsorption and desorption at 77K (-196℃). Figure 4 As shown in the figure, compared with UiO-66-F4 before encapsulation, the host-guest composite material [(N4Py)Fe IV =O]Cl2@UiO-66-F4 nitrogen adsorption capacity decreased significantly, which once again confirmed that the guest molecule ([(N4Py)Fe IV =O]Cl2) was successfully loaded in the pore structure of the main molecule (UiO-66-F4); the host-guest composite material of the above Example 2 was tested by TEM-EDS spectrum, as shown in Figure 5 As shown, from Figure A to Figure D, it can be seen that fluorine, zirconium and iron elements exist and are evenly distributed in the pores, proving that the guest molecules are evenly distributed in the main framework.

[0051] In order to further characterize the guest molecule ([(N4Py)Fe IV =O]Cl2) in the UiO-66-F4 channel, the host-guest system of Example 2 ([(N4Py)Fe IV =O]Cl2@UiO-66-F4) for solid UV testing. Figure 6 It can be seen that when the guest molecules ([(N4Py)Fe IV =O]Cl2), a characteristic peak appeared at 692nm, which was similar to that of pure [(N4Py)Fe IV =O]Cl2, which confirms that the guest molecules in the UiO-66-F4 pores exist in the form of tetravalent mononuclear iron complexes. Figure 1 In the method, the guest is a non-heme high-valent iron-oxo complex, and the host is a metal-organic framework material. The host and the guest are assembled to form a host-guest system.

[0052] In the description of the above embodiments, specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples.

[0053] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, characterized in that: The structural expression of the host-guest composite material is: [(N4Py)Fe IV =O]Cl2@UiO-66-F4; Among them, UiO-66-F4 is a metal organic framework compound, [(N4Py)Fe IV =O] 2+ It is a non-heme mononuclear high-valent iron complex. The host of the host-guest composite material is UiO-66-F4, and the guest is [(N4Py)Fe IV =O]Cl2; @ indicates that the composite material is a porous coordination polymer material assembled by host and guest.

2. A method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex, characterized in that: For preparing the host-guest composite material according to claim 1, comprising: Obtaining UiO-66-F4 powder and an acetonitrile solution containing a divalent mononuclear iron complex, wherein the divalent mononuclear iron complex is FeN4Py; Adding the UiO-66-F4 powder to the acetonitrile solution, stirring until FeN4Py enters the interior of the UiO-66-F4 structure, and obtaining FeN4Py@UiO-66-F4 after centrifugation and washing; The FeN4Py@UiO-66-F4 was placed in an acetonitrile aqueous solution containing ammonium cerium nitrate and allowed to stand for 30 to 60 minutes to obtain a structural expression of [(N4Py)Fe IV =O]Cl2@UiO-66-F4 said host-guest composite material.

3. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 2, characterized in that: In the process of adding the UiO-66-F4 powder to the acetonitrile solution, the molar ratio of UiO-66-F4 to FeN4Py is 1:(1-2.5).

4. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 3, characterized in that: The FeN4Py@UiO-66-F4 is placed in an acetonitrile aqueous solution containing ammonium cerium nitrate, and the molar ratio of FeN4Py to ammonium cerium nitrate is 1: (2-2.5).

5. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 4, characterized in that: The volume ratio of water to acetonitrile in the acetonitrile aqueous solution is 1:(1-3).

6. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 5, characterized in that: During the stirring process until FeN4Py enters the interior of the UiO-66-F4 structure, the stirring rate is 100-300 rpm and the stirring time is 12-50 hours.

7. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 6, characterized in that: The method of obtaining UiO-66-F4 powder comprises: Obtain a glacial acetic acid solution having a volume concentration of 60-70%; Adding tetrafluoroterephthalic acid and zirconium nitrate to the glacial acetic acid solution, and stirring until the solid powder is completely dissolved to obtain a mixed solution; the molar ratio of the tetrafluoroterephthalic acid to the zirconium nitrate is 1: (1-2); The mixed solution is condensed and refluxed at a temperature of 100-120° C. for 24-36 hours to form UiO-66-F4 with a cage-like porous structure; and the UiO-66-F4 is dried to obtain the UiO-66-F4 powder.

8. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 7, characterized in that: After forming the cage-like porous structure of UiO-66-F4 and before drying the UiO-66-F4, the method further comprises: Centrifuging the mixed solution to remove the mother liquor to obtain a powdered solid material; Washing the solid material with ultrapure water to remove the solution on the surface of the solid material; The solid material is then immersed in methanol, dichloromethane and acetonitrile for three days, with the solvent changed every day; the solid material is UiO-66-F4.

9. The method for preparing a host-guest composite material based on a metal organic framework material and a N4Py high-valent mononuclear iron complex according to claim 8, characterized in that: The drying of the UiO-66-F4 comprises: After the solid material was immersed in methanol, dichloromethane and acetonitrile for exchange for three days, the solid material was placed in a vacuum oven at 120° C. for 24 hours and cooled to room temperature to obtain the UiO-66-F4 powder.

10. Use of the host-guest composite material based on the metal organic framework material and the N4Py high-valent mononuclear iron complex according to claim 1 in the preparation of redox catalytic materials and bioinorganic chemical materials.

Citation Information

Patent Citations

  • Host-guest composite material based on cage-shaped porous material and TPA mononuclear iron complex as well as preparation method and application of host-guest composite material

    CN116396494A